Magnetically-coupled Current Sensor Using An Integrated Coil And A Cmos Split-drain Transistor - Castaldo, Fernando C.; dos Reis Filho, Carlos A. (Eletrônica de Potência, 2006)
An integrated current sensing circuit intended for Smart-Power and embedded applications featuring galvanic isolation is implemented. It is based on magnetic detection using the CMOS compatible Split- Drain transistor (MAGFET) that provides a very linear output current versus magnetic field. The current to be sensed flows through an integrated coil placed atop the split-drain transistor and produces a relatively strong magnetic coupling enough to cause a detectable transistor unbalance current. An integrated sensor built in 0.35ìm CMOS technology presented an output conversion factor of 1500nA/A and a minimum detectable magnetic field around 1ìT within 1Hz bandwidth in thermal range for 100ìA transistor bias current.